DESIGN AND IMPLEMENTATION OF LOCATION AND SITUATION BASED SERVICES FOR A PERVASIVE MOBILE ADVENTURE GAME - Kuehn, Eileen; Sieck, Juergen (International Journal of Computing, 2010)
This paper describes the design and implementation of a location and situation based pervasive mobile adventure game named Sportix. The prototype uses different types of sensor data – including 3D acceleration data and XPS – to determine the current position and activity of the player. Depending on the firm classification, data and quests are retrieved accordingly from a central information system and visualised for the player on the mobile device. By solving quests and performing sports the player is able to participate in the game.